2011
DOI: 10.1111/j.1574-695x.2011.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of chickens inoculated with a recombinant fowlpox vaccine coexpressing glycoprotein B of infectious laryngotracheitis virus and chicken IL-18

Abstract: Infectious laryngotracheitis virus (ILTV) is an alphaherpesvirus that causes severe and economically significant respiratory disease in poultry worldwide. Herein, the immunogenicity of two recombinant fowlpox viruses (rFPV-gB and rFPV-gB/IL18) containing ILTV glycoprotein B (gB) and chicken interleukin-18 (IL-18) were investigated in a challenge model. One-day-old specific-pathogen-free chickens were vaccinated by wing-web puncture with the two rFPVs and challenged with the virulent ILTV CG strain. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…IL-18 is a strong IFN-␥-inducing factor that enhances immune responses when used as an adjuvant. The concept of using IL-18 to boost immune responses after vaccination has been investigated for chicken vaccines (23,24,32,(36)(37)(38). Hung et al (21) described that the full-length and mature chicken IL-18 purified recombinant protein effectively enhanced cell-mediated and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 is a strong IFN-␥-inducing factor that enhances immune responses when used as an adjuvant. The concept of using IL-18 to boost immune responses after vaccination has been investigated for chicken vaccines (23,24,32,(36)(37)(38). Hung et al (21) described that the full-length and mature chicken IL-18 purified recombinant protein effectively enhanced cell-mediated and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 ϩ cells may directly produce antiviral cytokines, which increase B cell activity and promote the proliferation, maturation, and functional activity of CD8 ϩ CTLs, thus playing a critical role in controlling IBV infection (48,49). The ratio of CD4 ϩ /CD8 ϩ cells has been widely shown to be indicative of the general immune system status (50,51). In this study, the CD4 ϩ /CD8 ϩ ratio showed no significant (P Ͻ 0.05) variation among the groups until 14 doa.…”
Section: Fig 7 Means Of Histopathological Scores Of Lesions In Trachementioning
confidence: 99%
“…It has been shown that the ILTV gB protein assembles into homodimers that are rapidly cleaved to form two disulphide-linked species (20). Recombinant fowlpox virus-vector vaccines expressing the ILTV gB gene, and a DNA vaccine containing the gB gene, have also been developed and have been shown to provide protective immunity in chickens (3,7,26,30).…”
mentioning
confidence: 99%